Pengaruh Latihan Burpee Terhadap Daya Tahan Otot dan Kardiovaskular Mahasiswa Ilmu Keolahragaan - Muhamad Ihsan Kamal Ihsan; Iman Imanudin; Mohammad Zaky (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of burpee exercise on muscular endurance and cardiovascular fitness in sports science students. The method used was a quasi-experimental design with a one group pretest-posttest approach. The subjects consisted of 10 students from the Faculty of Sports Science, Universitas Pendidikan Indonesia, selected using purposive sampling based on specific criteria. The instruments included push-up, sit-up, and hurdle jump tests to measure muscular endurance, and the 15-minute Balke Test to assess cardiovascular fitness. The treatment was a burpee exercise program conducted for 6 weeks with a frequency of three sessions per week. The results showed improvements in cardiovascular fitness as indicated by increased VO₂max, as well as enhancements in all components of muscular endurance. Statistical analysis revealed a significant effect of burpee exercise on both muscular endurance and cardiovascular fitness. In conclusion, burpee exercise is an effective training method to improve muscular endurance and cardiovascular fitness in students Keywords: Burpee, Muscular Endurance, Cardiovascular Fitness, Physical Training, VO₂Max